1991
DOI: 10.1104/pp.95.1.234
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Leaf Abscission in Cotton Is a Common Effect of Urea- and Adenine-Type Cytokinins

Abstract: Cytokinins of the urea and adenine type induced leaf abscission in young cotton (Gossypium hirsutum) plants in the following order of activity: N-phenyl-N'-1,2,3-thiadiazol-5-ylurea (thidiazuron) >> N-phenyl-N'-(2-chloro-4-pyridyl)urea > isopentenyladenine > 6-benzyladenine > zeatin = dihydrozeatin > kinetin. It is suggested that ethylene production is implicated in this response because it was stimulated by the compounds in cotton leaf discs with nearly the same effectiveness. Moreover, similar to thidiazuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…The inability of ACC and the cytokinins, each applied alone, to stimulate ethylene biosynthesis together with the notable enhanced ethylene production following treatment of seeds with cytokinin-ACC combinations (Tabs 1 and 2) indicate that treatment with cytokinins increases the capacity of the seeds to convert ACC into ethylene. This is consistent with several reports on stimulation of ACC oxidation in plant seeds and vegetative parts following enhancement of ACC oxidase activity by cytokinins (Suttle 1986, Yip and Yang 1986, Khan and Huang 1988, Grossman 1991. The relative activity of the cytokinins on ACC oxidation, as revealed by the ethylene released, was TDZ > TZ > BA > KIN.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The inability of ACC and the cytokinins, each applied alone, to stimulate ethylene biosynthesis together with the notable enhanced ethylene production following treatment of seeds with cytokinin-ACC combinations (Tabs 1 and 2) indicate that treatment with cytokinins increases the capacity of the seeds to convert ACC into ethylene. This is consistent with several reports on stimulation of ACC oxidation in plant seeds and vegetative parts following enhancement of ACC oxidase activity by cytokinins (Suttle 1986, Yip and Yang 1986, Khan and Huang 1988, Grossman 1991. The relative activity of the cytokinins on ACC oxidation, as revealed by the ethylene released, was TDZ > TZ > BA > KIN.…”
Section: Discussionsupporting
confidence: 92%
“…The relative activity of the cytokinins on ACC oxidation, as revealed by the ethylene released, was TDZ > TZ > BA > KIN. This order of activity is similar to that reported by Suttle (1986) and Grossman (1991) for elicitation of ethylene from cotton leaf discs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was firstly used as a defoliant for cotton. Premature activation of the abscission zone affects water potential or chlorophyll content in some members of Malvaceae family (Grossmann, 1991). Although, TDZ protected chlorophyll degradation in detached leaves of geranium (Murthy et al, 1998;Visser et al, 1995).…”
Section: Tdz Liaised Responsesmentioning
confidence: 99%
“…In addition, there are still some problems in the practical use of defoliant, for example, the leaves dehydrated but not shed, and the effect of defoliants being tightly associated with the application schedule, dosage, and air temperature. Early studies showed that adenine cytokinins could induce cotton leaves abscission by increasing the content of ethylene [29,30]. Botton et al also reported that cytokinin (ben-zyladenine, BA), could cause fruits abscission by crosstalk signaling pathways, mainly involving sugars, ROS, ABA, and ethylene [31].…”
mentioning
confidence: 99%